FOREWORD - Daniela, Nelva; Ulrich, Silvia (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2018)
Forword to CrOCEVIA • "Memories and Generations: A Prismatic View", edited by Daniela NELVA & Silvia ULRICH